Urine 1H-NMR Metabolomics to Discriminate Neurocysticercosis Patients from Healthy Controls: An Exploratory Study - Lopez, J.M.; Leyva, V.E.; Bustos, J.A.; Perez, E.; Sanchez-Boluarte, S.S.; Saavedra, H.; Gonzales, I.; Maruenda, H.; García, H.H. (American Society of Tropical Medicine and Hygiene, 2022)
ABSTRACT. The diagnosis of neurocysticercosis (NCC) is principally based on neuroimaging (magnetic resonance imaging or computed tomography), instrumentation that is scarcely available in the rural regions where Taenia solium transmission, primarily occurs due to poor sanitation conditions. Immunological assays for antigen or antibody detection complement the neuroimaging approach. However, no field-applicable assays to diagnose viable NCC or to guide the referral of cases for neuroimaging or for appropriate management are available. We performed an exploratory study on urine and serum samples using 1 H-nuclear magnetic resonance (NMR)-based metabolomics to discriminate NCC patients ( n = 14) from healthy control subjects ( n = 22). Metabolic profiles demonstrated a discrimination between the urines of NCC patients and noninfected control subjects with a moderate predictive accuracy ( R 2 = 0.999, Q 2 = 0.434). NMR metabolomics analysis has been proven useful in depicting biomarkers linked to other infectious diseases, various types of cancer, and other disorders. Our results, albeit preliminary, open a door to the development of better methods for detecting NCC through the identification of biomarkers participating in disturbed metabolic pathways.
Keywords: Neurocysticercosis; Taenia solium; Metabolomics; Neuroimaging; Medicine; Magnetic resonance imaging; Cysticercosis; Urine; Biomarker; Pathology; Internal medicine; Radiology; Biology; Bioinformatics; Psychiatry; Biochemistry; https://purl.org/pe-repo/ocde/ford#3.02.00